Public aid as part of the restructuring procedure: Private creditor test exemplified by limited liability company under restructuring - Edyta Piątek; Magdalena Konat-Staniek (Economic and Environmental Studies (E&ES), 2018)
When the new Restructuring Law entered into force on 1 January 2016, it opened a lot of possibilities for entrepreneurs to use aid for the purpose of keeping a company on the market. As part of the procedure, it is necessary to determine whether the granted aid does not constitute incompatible public aid that disrupts free market rules. The answer to this issue is provided by the private creditor test and the private investor test. The objective of the article is to present the developed method of a private creditor test for the restructuring of a company in which one of the authors participated as an auditor. The article presents the method which allows verification of justifiability of participation of a public creditor in the process of debtor restructuring. The method was developed on the basis of hitherto studies and practical experience of the authors. The Wilcox method was used in one of the test stages to assess property. The prepared method has been successfully applied in other cases of company restructuring, and the case presented in this article is used to explain the principles of operation.
Keywords: 330; restructuring; creditor's test; de minimis aid